Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Budaya Organisasi terhadap Kinerja Karyawan Pada PT. Bank BNI Syariah Palu - Hariyanto Ramli Djatola (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2019)
This research aims to (1) know and analyse The effect of leadership style, work motivation and organizational culture on staff performance of PT. Bank BNI Syariah Palu; (2) know and analyse the effect of leadership style on staff performance of PT. Bank BNI Syariah Palu; (3) know and analyse the effect of work motivation on staff performance PT. Bank BNI Syariah Palu; (4) know and analyse the effect of organizational culture on staff performance of PT. Bank BNI Syariah Palu. Population in this research is 45 staff, and all of them become sample. Data in this research is analyzed by using multiple linear regression. The result shows that (1) leadership style, work motivation and organizational culture simultaneously perform positive and significant effect on staff performance of PT. Bank BNI Syariah Palu; (2) leadership style performs positive and significant effect on staff performance of PT. Bank BNI Syariah Palu; (3) work motivation performs positive and significant effect on staff performance of PT. Bank BNI Syariah Palu; and (4) organizational culture performs positive and significant effect on staff performance of PT. Bank BNI Syariah Palu.